2007
DOI: 10.1007/s11746-007-1149-y
|View full text |Cite
|
Sign up to set email alerts
|

Free‐Radical‐Scavenging Effect of Carbazole Derivatives on DPPH and ABTS Radicals

Abstract: The major objective was to measure the trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid) equivalent antioxidant capacity (TEAC) of carbazole derivatives (Ar 2 NHs) by means of scavenging 2,2 0 -diphenyl-1-picrylhydrazyl (DPPH) and the 2,2 0 -azinobis(3-ethylbenzothiazoline-6-sulfonate) radical cation (ABTS +Á ). The Ar 2 NHs included phenoxazine (PozNH), phenothiazine (PtzNH), iminostilbene (IsbNH) and diphenylamine (DpaNH), and the TEAC of trolox, a-tocopherol (TocH), L-ascorbic acid (VC) and L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 23 publications
6
50
0
Order By: Relevance
“…However, the effect was relatively lower compared with that ascorbic acid and Tiron at the concentrations similar to that used during the compound evaluation. The DPPH radical is a compound that has been widely used to test the free radical scavenging ability of various substances (35)(36)(37)(38)(39). The radical decreases in the presence of proton radical scavengers (40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect was relatively lower compared with that ascorbic acid and Tiron at the concentrations similar to that used during the compound evaluation. The DPPH radical is a compound that has been widely used to test the free radical scavenging ability of various substances (35)(36)(37)(38)(39). The radical decreases in the presence of proton radical scavengers (40).…”
Section: Resultsmentioning
confidence: 99%
“…• is a result of the competition of two mechanisms, hydrogen transfer and sequential proton loss electron transfer (36). The last mechanism suggest that partial ionization of the antioxidant can enhance proton transfer to DPPH • .…”
Section: Resultsmentioning
confidence: 99%
“…AAPH was dissolved in phosphate-buffered solution (PBS: 8.1 mM Na 2 HPO 4 , 1.9 mM NaH 2 PO 4 , 10 mM EDTA, pH 7.4). The other two radical-related solutions were prepared as described [Tang and Liu, 2007a]. Briefly, DPPH was dissolved in ethanol ($100 mM) to give an absorbance $1.00 at 517 nm (Abs ref ).…”
Section: Methodsmentioning
confidence: 99%
“…The reactions between DaH (or its sodium salt) and ABTS þ: , DPPH were carried out as previously described [Tang and Liu, 2007a] [Tang and Liu, 2007a].…”
Section: And Dpphmentioning
confidence: 99%
“…The mechanism(s) for free radical scavenging is not known exactly; however probable mechanism(s) involve the interaction between the hydroxyl functional group of the carbazole derivatives and the DPPH; where sequential proton loss electron transfer (SPLET) is an indication of the ability of the antioxidant to scavenge free radicals. 25 The study highlighted that the structure has a key influence on biological activity. The structureactivity relationship may be established where it was observed that carbazole scaffold remained a foremost need for exhibiting anti-oxidant activity.…”
Section: Anti-oxidant Activitymentioning
confidence: 99%